L’expertise, composante essentielle mais insuffisante des stratégies pour la biodiversité : le cas de la démoustication en Camargue (France) - Fanny Guillet; Laurent Mermet (VertigO, 2013)
Because of its interest for biodiversity conservation, the Camargue remained outside the mosquito control zone, between Marseille and the Spanish border, until 2005. The mosquito control is nevertheless initiated in the territory, due to the demand for solution emerging from local communities, mainly tourism professionals, especially in the aftermath of exceptional mosquito outbreak in autumn 2005. The environmental actors obtained an impact assessment to be realized. Starting from this case study, this paper analyse the three-way relationship between public authorities, their experts and the actor participating in the independent scientific expertise in this biodiversity issue. The analysis is performed within the theoretical framework of the strategic environmental management analysis (Mermet et al., 2005), focusing on strategies of the different stakeholders managing a territory and on the differentiation of role they are playing concerning the environmental issue. It will be shown that politicians can ignore their own involvement, thanks to the scientific expertise that have been establish by the political and administrative system. It will also be demonstrate the presence of environmental actors integrating the independent expertise in their strategic action for the environment is decisive since biodiversity is threatened. The function of independent scientific expertise, as spokesman of the biodiversity in the public arena, is coming in different strategic and complementary roles detailed in the article.